2011
DOI: 10.1371/journal.pone.0023194
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Inhibits Neuronal and Vascular Degeneration in Retina after Ischemia and Reperfusion Injury

Abstract: BackgroundNeuron loss, glial activation and vascular degeneration are common sequelae of ischemia-reperfusion (I/R) injury in ocular diseases. The present study was conducted to explore the ability of curcumin to inhibit retinal I/R injury, and to investigate underlying mechanisms of the drug effects.Methodology/Principal FindingsDifferent dosages of curcumin were administered. I/R injury was induced by elevating the intraocular pressure for 60 min followed by reperfusion. Cell bodies, brn3a stained cells and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
78
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(84 citation statements)
references
References 41 publications
4
78
0
2
Order By: Relevance
“…In I/R retina, Müller cell gliosis and hypertrophy are complications that worsen the pathological conditions. Retinal Müller cells exhibit hypertrophic morphology and increased expression of GFAP in ocular diseases such as retinal I/R injury 57,58 and diabetic retinopathy. 59 In fact, a Müller cell is one of the primary sources of pro-inflammatory cytokine during injuries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In I/R retina, Müller cell gliosis and hypertrophy are complications that worsen the pathological conditions. Retinal Müller cells exhibit hypertrophic morphology and increased expression of GFAP in ocular diseases such as retinal I/R injury 57,58 and diabetic retinopathy. 59 In fact, a Müller cell is one of the primary sources of pro-inflammatory cytokine during injuries.…”
Section: Discussionmentioning
confidence: 99%
“…58,59,[67][68][69] We speculated that lutein inhibits IL1b and Cox-2 expression through the reduction of NF-jB nuclear translocation in rMC-1 cells. Indeed, our findings demonstrated that expression of the active form of NF-jB, P-NF-jB, was up-regulated in nuclear extract after CoCl 2 -induced hypoxia, indicating the activation of NF-jB signaling similar to that in human skin keratinocytes (HaCaT cells).…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin protected cultured neuronal cells against death induced by iodoacetate, an inhibitor of glycolysis (Reyes-Fermín et al, 2012). Curcumin treatment also reduced neuronal and microvessel degeneration in the retina in a rat model of ischemiareperfusion injury (Wang et al, 2011c). Catechins protected cultured neurons against death induced by the mitochondrial toxin 3-nitropropionic acid (3NP) (Nath et al, 2012).…”
Section: B Metabolic Stressmentioning
confidence: 99%
“…Previous studies have demonstrated that curcumin attenuates I/R injury in various organs in vivo and in vitro, including the intestines, retina, liver and renal system, through anti-oxidative stress and anti-apoptotic mechanisms (20)(21)(22)(23) through the attenuation of oxidative stress and mitochondrial dysfunction. However, the beneficial effects of curcumin on the extent of apoptosis and autophagy in myocardial I/R, and their potential mechanisms, remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%